Transformation Evaluation Mathematics : From Exams Summative to Evaluation Formative Based Technology - Johan Johan; Herman Herman (Gema Cendekia Institute, 2025)
Development digital technology has bring change significant in paradigm evaluation education , including on field learning mathematics . Research This aim For analyzing the transformation process evaluation mathematics from approach traditional based exam summative going to system evaluation formative based more technology​ adaptive And sustainable . Method research used​ is studies literature with approach descriptive-analytical to various results study latest about implementation evaluation digital formative , such as use of Learning Management Systems (LMS), applications based on Artificial Intelligence (AI), and assessment online interactive . Results study show that evaluation formative based technology capable give bait more back​ fast , accurate , and personal to participant educate , so that support learning more mathematics​ meaningful And reflective . Besides that , use technology allows teachers to do monitoring development competence student in real-time as well identify difficulty Study in a way early . However , the transformation This Also face challenges , such as teacher readiness in digital literacy , availability infrastructure technology , and justice access for all over participant educate . In conclusion , the assessment formative based technology is step strategic in increase effectiveness learning mathematics , as long as accompanied with strengthening digital competence of teachers and support policy Continuing Education.